2020
DOI: 10.1101/2020.03.16.993683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphic SNPs, short tandem repeats and structural variants are responsible for differential gene expression across C57BL/6 and C57BL/10 substrains

Abstract: C57BL/6J is the most widely used inbred mouse strain and is the basis for the mouse reference genome. In addition to C57BL/6J, several other C57BL/6 and C57BL/10 substrains exist. Previous studies have documented extensive phenotypic and genetic differences among these substrains, which are presumed to be due to the accumulation of new mutations. These differences can be used for genome wide association studies.They can also have unintended consequences for reproducibility when substrain differences are not pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…These two lines also did not have higher rates of SNPs or small indels than other lines (Mortazavi et al 2020). However, C57BL/6NHsd had the highest number of large-scale deletions found by CNVnator, and C57BL/6NJ had the highest number of duplications called by Lumpy (Mortazavi et al 2020), concordant with the direction of gains and losses of kmers that we found. Figure 4.…”
Section: Complex Pericentromeric Satellites Have Similar Mutation Ratsupporting
confidence: 84%
See 4 more Smart Citations
“…These two lines also did not have higher rates of SNPs or small indels than other lines (Mortazavi et al 2020). However, C57BL/6NHsd had the highest number of large-scale deletions found by CNVnator, and C57BL/6NJ had the highest number of duplications called by Lumpy (Mortazavi et al 2020), concordant with the direction of gains and losses of kmers that we found. Figure 4.…”
Section: Complex Pericentromeric Satellites Have Similar Mutation Ratsupporting
confidence: 84%
“…Relevant scripts used to analyze the data are available here: https://github.com/jmf422/BL6_mouse_satellites Mouse sequencing Data used are from (Mortazavi et al 2020). In brief, DNA from 1 male per strain was extracted from spleens.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations